Lactobacillus plantarum L-137 and/or β-glucan impacted the histopathological, antioxidant, immune-related genes and resistance of Nile tilapia (Oreochromis niloticus) against Aeromonas hydrophila - Mahmoud A.O. Dawood (2020)
© 2020 Elsevier Ltd A trial was operated to assess the potential of using Lactobacillus plantarum L-137 (L-137) and/or β-glucan (BG) in improving the resistance of Nile tilapia against Aeromonas hydrophila. Control diet and 3 diets supplemented with L-137, BG or L-137 + BG were prepared. Final body weight, specific growth rate, superoxide dismutase, and catalase showed considerably (P < .05) increased values in L-137 or L-137/BG groups, while glutathione peroxidase increased significantly (P < .05) only in L-137/BG group. Fish fed L-137 and/or BG diets showed that feed conversion ratio and malonaldehyde levels were significantly decreased (P < .05). Also, both L-137 and BG helped Nile tilapia to have high phagocytosis activity and relative expression of tumor necrosis factor-alpha (TNF-α) and interleukin 1 beta (IL-1β) and interferon-gamma (INF-γ) genes. After A. hydrophila challenge, the intestinal villi epithelium of the L-137/BG group was intact and denser than the other groups. The hepatopancreas and spleen of the control group displayed severe necrosis in hepatocytes and congestion of blood sinusoids in addition to diffuse vacuolation. Regarding the L-137, BG and L-137/BG groups, there was a moderate and normal degree of vacuolation with focal necrosis and mild to moderate degree of congestion of blood sinusoids. Red blood cells, hemoglobin, and albumin showed meaningfully (P < .05) increased values in L-137 or L-137/BG groups. TNF-α, IL-1β, and INF-γ expressions were upregulated by L-137 and/or BG. The obtained results revealed the ability of L-137 and/or BG to protect Nile tilapia from the effects of A. hydrophila infection by the motivation of the immune, antioxidative, and antiinflammation responses.